2015
DOI: 10.1128/jcm.02950-14
|View full text |Cite|
|
Sign up to set email alerts
|

Utility of Sequencing the erm (41) Gene in Isolates of Mycobacterium abscessus subsp. abscessus with Low and Intermediate Clarithromycin MICs

Abstract: bThe erm(41) gene confers inducible macrolide resistance in Mycobacterium abscessus subsp. abscessus, calling into question the usefulness of macrolides for treating M. abscessus subsp. abscessus infections. With an extended incubation (14 days), isolates with MICs of >8 g/ml are considered macrolide resistant by current CLSI guidelines. Our goals were to determine the incidence of macrolide susceptibility in U.S. isolates, the validity of currently accepted MIC breakpoints, and the erm(41) sequences associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
126
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(140 citation statements)
references
References 14 publications
10
126
3
1
Order By: Relevance
“…Similarly, assignment of the T or C SNP at position 28 of erm(41) by our real-time SNP assay showed 100% concordance to erm(41) gene sequencing. In this study, the majority (93% [64/69]) of the isolates with full-length erm(41) had a T at position 28, and 7% (5/69) had a C. Thus, the rate of inactive C28 erm(41) in our study (7%) is lower than the recently reported rate of 18% of M. abscessus with an inactive C28 erm(41) sequevar (28).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Similarly, assignment of the T or C SNP at position 28 of erm(41) by our real-time SNP assay showed 100% concordance to erm(41) gene sequencing. In this study, the majority (93% [64/69]) of the isolates with full-length erm(41) had a T at position 28, and 7% (5/69) had a C. Thus, the rate of inactive C28 erm(41) in our study (7%) is lower than the recently reported rate of 18% of M. abscessus with an inactive C28 erm(41) sequevar (28).…”
Section: Discussioncontrasting
confidence: 53%
“…Another explanation lies in the technical challenges of this test. In a recent article, Brown-Elliott et al (28) reported that some C28 isolates with a MIC of 8 upon extended incubation showed a MIC of Յ2 g/ml upon repeat testing. In the same study, the authors proposed to change clarithromycin susceptibility breakpoints from Յ2 g/ml to Յ4 g/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeat pDST revealed resistance for all three isolates. This finding indicates that discrepancies between genetic and phenotypic susceptibility testing of M. abscessus often relate to problems of poor growth and difficulties in interpreting MICs, and not to errors in genetic assays [22].…”
Section: Discussionmentioning
confidence: 91%
“…This is particularly important when determining susceptibility for M. abscessus as resistance is not exclusively due to mutations, but may result from other mechanisms such as upregulated drug export systems or decreased cell wall permeability [26]. On the other hand, pDST interpretation can be difficult for rapidly-growing mycobacteria as poor growth can lead to falsely susceptible results [22]. In this case GenoType® NTM DR can help to improve the interpretation of pDST results by supporting or refuting them.…”
Section: Discussionmentioning
confidence: 99%